ANALISIS METODE TERJEMAHAN DALAM AL-QUR’ANUL KARIM BACAAN MULIA KARYA HB. JASSIN - Sarmila Mila; Aisah Sumaiyah Siregar (Amsal Al-Qur’an: Jurnal Al-Qur’an dan Hadis, 2026)
This study aims to analyze the translation methods used in Al-Qur’anul Karim Bacaan Mulia by HB. Jassin, a translation of the Qur’an known for its literary approach and has generated various responses regarding the fidelity of meaning and the beauty of language. The background of this study is based on the importance of understanding the characteristics of translation methods applied in religious texts, especially when the aesthetic elements of language are the main concern of the translator. The study uses a qualitative descriptive method with a literature study approach. Data were obtained from the translated text of Al-Qur’anul Karim Bacaan Mulia and analyzed based on the theory of translation methods to identify the tendencies of strategies used by HB. Jassin in transferring the message of the Qur’an into Indonesian. The results of the study show that HB. Jassin tends to apply translation methods that are oriented towards the target language by emphasizing the aesthetic aspects, rhythm, and style of literary language, resulting in a more communicative and poetic translation. However, this approach in some parts causes a shift in meaning and a reduced level of literalness compared to more literal translations of the Qur’an. Thus, the translation of HB. Jassin can be understood as an attempt to present the message of the Qur'an through a literary approach without completely abandoning the substantive meaning of the source text.